Impact of Ocean Acidification on Calcifying Marine Organisms: Implications for Growth, Structure, and Fisheries - Weng Yuzhao; Zhou Liyan (MATEC Web of Conferences)
Rising CO2 emissions drive ocean acidification, leading to a decline in carbonate ion concentration and a reduction in calcium carbonate saturation, which negatively impacts marine organisms that rely on calcification for growth and survival. This paper examines how declining calcium carbonate saturation impacts corals, molluscs, and other calcifying species. The results show that the lower saturation levels impede the formation of the shell and the skeleton, leading to a slower growth rate, a structural abnormality, and an increased risk of dissolution. The main results indicate that young corals with a high PCO2 content have decreased bone thickness and diameter. In addition, there is a decline in the number of commercially farmed fish, such as shrimps and scallops, which poses a threat to food safety and the world fishing economy. By analyzing the chemical, ecological, and economic impacts, this study emphasizes the need for CO2 emission reductions and sustainable practices.